2019
DOI: 10.1111/jgs.15889
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Smoking Status on the Health Profiles of Older Chinese American Men

Abstract: OBJECTIVE: To examine the influence of smoking status on the health profiles of community-dwelling older Chinese American men in the greater Chicago, IL, area. DESIGN: This study utilized a cross-sectional study design to analyze data obtained from the larger Population Study of Chinese Elderly in Chicago (PINE). SETTING: A population-based study conducted in Chicago. PARTICIPANTS: Baseline data from Chinese American men who participated in PINE (N = 1492). MEASURES: Demographic characteristics measured includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Our findings are consistent with previous research linking smoking to poor physical and mental health [15,18,19,[48][49][50][51][52][53]. Specifically, it has been shown that both current and former smokers are at increased risk for depression [31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with previous research linking smoking to poor physical and mental health [15,18,19,[48][49][50][51][52][53]. Specifically, it has been shown that both current and former smokers are at increased risk for depression [31].…”
Section: Discussionsupporting
confidence: 92%
“…With regard to the risk of late life depression, very few studies have examined the association between substance consumption behavior and the risk of late life depression [14][15][16]. While there is evidence that smoking is associated with severity of depression in older individuals [15,[17][18][19], research findings are inconsistent regarding alcohol consumption. A number of studies found no association between depressive symptoms and alcohol consumption [14,15,[20][21][22][23], while some researchers found an inverse association between alcohol use and depression severity [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor: We would like to thank Flores and Simon for their interest in our initial letter regarding the Home-Oriented Ultrasound Examination (HOUSE) protocol. 1 They raise several opportunities for additional point-of-care ultrasound (POCUS) modalities as useful in the home visit including examinations of soft tissue, the musculoskeletal system, and the abdomen. 2 Our initial cohort of 16 patients was drawn from a population heavily composed of those receiving highdose diuretic therapy at home (75%).…”
Section: Reply To: Using Point-of-care Ultrasound On Home Visitsmentioning
confidence: 99%
“…Regarding social relationships, three articles concentrate on various facets of the social contexts of Chinese families including filial piety from the perspectives of the older adult and their adult children and older adults' capability for social engagement . Lastly, two articles explore patterns of health behaviors among Chinese older adults to understand potential predictors and consequences of certain health behaviors …”
mentioning
confidence: 99%